Discipline and Subjectivity in Religious Education - Asimiadis, Dionysios (Greek Journal of Religious Education (GjRE), 2025)
The paper examines the relationship between disciplinary power and subject formation in Religious Education through the theoretical insights of Michel Foucault. The general objective is to discuss how curriculum and pedagogy in Religious Education are engaged in the process of constructing normalized religious subjects through discipline, surveillance, and internalization. The reason behind such a focus is the need to critically analyze the unseen power relations that constitute pedagogical space and student identity. The paper analyzes relevant curricular texts and pedagogic practices and how they illustrate the functioning of knowledge-power relations within classroom space. Some of the findings point towards Religious Education, albeit unintentional, as a reproducing and normalizing ideological space. The review concludes by suggesting ways of change and resistance in the form of more participatory and reflexive pedagogical paradigms. The current paper adds to the literature on educational subjectivation with critical significance to teachers, researchers, and curriculum planners who are interested in democratic and emancipatory religious education.